Design of a Drug Policy Model Based on Community Participation to Realize a Drug-Free Indonesia (BERSINAR) - Djaba, Misbahudin; Mohi, Elnino M. Husein; Katili, Andi Yusuf (Publik : (Jurnal Ilmu Administrasi), 2025)
Repressive approaches alone have proven insufficient in curbing drug distribution and abuse. Therefore, a participatory and context-sensitive approach that positions communities as key actors is urgently needed. This study aims to analyze the implementation of community participation-based narcotics policy in Gorontalo Province and formulate a policy model that places the community as an active subject in the Prevention and Eradication of Drug Abuse and Illicit Trafficking (P4GN) program. A qualitative descriptive approach was chosen to explore the institutional and social dynamics within program implementation. Findings show that implementing P4GN in Gorontalo is suboptimal due to limited organizational capacity at BNNP and the lack of meaningful community engagement in programs such as Volunteers, Anti-Drug Activists, and Shining Villages. This research formulates a policy model integrating Asset-Based Community Development (ABCD) and Deliberative Democracy frameworks. The model emphasizes strengthening internal community assets (human, social, financial, physical, and natural) alongside external dimensions (influence, representation, and deliberation). This dual focus aims to enhance community resilience and ensure active involvement in drug policy formulation and implementation. This study's novelty lies in its structured, deliberative, and asset-oriented community participation model for narcotics policy. This approach remains underdeveloped in Indonesian research and has the potential to be replicated across other vulnerable regions.